Firms and Labor in Times of Violence: Evidence from the Mexican Drug War - Hale Utar (Institute of Labor Economics (IZA), 2022)
This paper examines how firms in an emerging economy are affected by violence due to drug trafficking. Employing rich longitudinal plant-level data covering all of Mexico from 2005–2010, and using an instrumental variable strategy that exploits plausibly exogenous spatiotemporal variation in the homicide rate during the outbreak of drug-trade related violence in Mexico, I show that violence has a significant negative impact on plant output, product scope, employment, and capacity utilization. Resilience to violence differs widely across different types of employment within firms and across firms with different characteristics. Employment decline is driven by bluecollar employment only. Dissecting within- and cross-plant heterogeneity points to a local labor supply channel where particularly plants utilizing low-wage, female, blue-collar workers are impacted. Consistent with a blue-collar labor supply shock, the results show a positive impact on average blue-collar wages and a negative impact on average white-collar wages at the firm level. Output elasticity of violence is also shown to be larger among low-wage, female-intensive but also domestically buying and selling plants. These findings show the rise of drug violence has significant distortive effects on domestic industrial development in Mexico and shed light on the characteristics of the most affected firms and the channels through which they are affected.
Keywords: L25; L60; O12; O14; O18; O19; R11; O54; F14; 330; firms; violence; organized crime; manufacturing; drug war; Mexico; labor; technology; productivity; reallocation; gender